2012
DOI: 10.1371/journal.pone.0042800
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuronal Cells Generated by Human Parthenogenetic Stem Cells

Abstract: Parent of origin imprints on the genome have been implicated in the regulation of neural cell type differentiation. The ability of human parthenogenetic (PG) embryonic stem cells (hpESCs) to undergo neural lineage and cell type-specific differentiation is undefined. We determined the potential of hpESCs to differentiate into various neural subtypes. Concurrently, we examined DNA methylation and expression status of imprinted genes. Under culture conditions promoting neural differentiation, hpESC-derived neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
2
9
0
1
Order By: Relevance
“…Hence, our results confirm the potential of hESCs to differentiate into neural cells. These results are consistent with previous studies[16]. In a study by Zhang et al[15], hESCs differentiated to form neural tube-like rosette structures by day 7 of cell culture in a defined medium.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, our results confirm the potential of hESCs to differentiate into neural cells. These results are consistent with previous studies[16]. In a study by Zhang et al[15], hESCs differentiated to form neural tube-like rosette structures by day 7 of cell culture in a defined medium.…”
Section: Discussionsupporting
confidence: 93%
“…PG hESCs exhibited typical hESC morphology, expressed pluripotencyrelated markers and formed neural rosettes and NSCs when subjected to a multistep differentiation protocol (Figures 1A, B, Supplementary Figure 1) as described previously (12). HLA fine typing revealed that the PG hESC lines used in this study were fully heterozygous in the HLA region (Table 1).…”
Section: Pg Hesc-derived Nscs Express Hla-i But Not Hla-dr Antigenssupporting
confidence: 75%
“…PG and N hESC lines were cultured on feeders (human foreskin fibroblasts [ATCC-LGC Standards, Wesel, Germany] or murine embryonic fibroblasts) treated with mitomycin C (SigmaAldrich, St. Louis, MO, USA). Cells were differentiated into the neural lineage as described (12 . 20 ng/mL fibronectin (Sigma-Aldrich) and 10 ng/mL FGF2 were added freshly.…”
Section: Cell Lines and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In der Tat wurde berichtet, dass sich PG-ESZellen in ihrer Fähigkeit zur Selbsterneuerung und ihrem Differenzierungspotenzial ähnlich wie normale ES-Zellen verhalten (Koch et al, 2009;Ahmad et al, 2012). Dies bedeutet, dass für die Bildung funktioneller Neurone ein rein maternales Genom prinzipiell ausreichend ist.…”
Section: Mesenchymale Stamm-/stromazellen (Mscs)unclassified